Integrating Character Education through Peer Interactions: Challenges and Opportunities in a Modern Islamic Boarding School in Indonesia - Wahono Wahono; Nur Hidayah; Zulkarnain Zulkarnain; Endang Sri Radjeki (AL-ISHLAH: Jurnal Pendidikan, 2025)
Modern Islamic boarding schools (pesantren) aim to integrate character education into daily student life, yet the role of peer interactions in shaping moral development remains underexplored. This study investigates how peer relationships support or hinder character formation in a contemporary pesantren context. A sequential explanatory mixed-methods design was employed at Pondok Modern Ponorogo. The quantitative phase involved 212 students completing a validated Likert-scale questionnaire assessing three dimensions: Peer Support, Collaborative Learning, and Moral Challenges (Cronbach’s α = 0.926). The qualitative phase included semi-structured interviews with 15 purposively selected students to explain the patterns found in the survey. Data were analyzed using descriptive statistics and thematic analysis. Survey findings revealed generally high levels of peer support and collaborative learning, alongside substantial exposure to moral challenges such as peer pressure, gossip, and conformity. Interviews explained how peer interactions reinforce religious practice, emotional resilience, and teamwork, but also revealed experiences of exclusion, stress, and ethical ambiguity. Students identified both positive and negative peer influences as central to their character development. Peer interactions in pesantren function as a double-edged force: they can promote moral growth through encouragement and collaboration but can also undermine integrity when negative norms dominate. Structured peer mentoring, accountable group work, and ethical reflection sessions are recommended to harness peer influence constructively. This study offers actionable strategies for educators seeking to embed character education within Islamic boarding school life through context-sensitive, peer-driven approaches.